2000
DOI: 10.1161/01.atv.20.2.317
|View full text |Cite
|
Sign up to set email alerts
|

Warfarin-Induced Artery Calcification Is Accelerated by Growth and Vitamin D

Abstract: Abstract-The present studies demonstrate that growth and vitamin D treatment enhance the extent of artery calcification in rats given sufficient doses of Warfarin to inhibit ␥-carboxylation of matrix Gla protein, a calcification inhibitor known to be expressed by smooth muscle cells and macrophages in the artery wall. The first series of experiments examined the influence of age and growth status on artery calcification in Warfarin-treated rats. Treatment for 2 weeks with Warfarin caused massive focal calcific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

12
170
0
10

Year Published

2004
2004
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 221 publications
(192 citation statements)
references
References 48 publications
12
170
0
10
Order By: Relevance
“…Jie et al have reported in a population-based study of postmenopausal women that those with calcified lesions had lower intakes of phylloquinone and impaired vitamin K status than those without lesions (Jie et al, 1995). Vitamin K antagonists, such as warfarin, accelerate calcification of arteries in rat models (Price et al, 2000), whereas there are no comparable data currently available in humans. In the present study, the phylloquinone intake was inversely associated with nonfatal MI, which might be primarily associated with atherosclerosis-related mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…Jie et al have reported in a population-based study of postmenopausal women that those with calcified lesions had lower intakes of phylloquinone and impaired vitamin K status than those without lesions (Jie et al, 1995). Vitamin K antagonists, such as warfarin, accelerate calcification of arteries in rat models (Price et al, 2000), whereas there are no comparable data currently available in humans. In the present study, the phylloquinone intake was inversely associated with nonfatal MI, which might be primarily associated with atherosclerosis-related mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…Samples of the abdominal aorta, the heart, the right lung, and the remnant kidney were fixed in 10% buffered formalin and subsequently sectioned and stained for mineralization by the von Kossa method. Another portion of the aorta was demineralized in 10% formic acid, and the arterial tissue Ca and P content was measured in the supernatant according to the method described by Price et al (21). Quantification of tissue mineral content was performed as described previously (22).…”
Section: Assessment Of Vascular and Soft Tissue Calcificationmentioning
confidence: 99%
“…Reprinted from reference (64), with permission. min K for ␥-carboxylation, acquired vitamin K deficiency, as with the use of warfarin, may predispose to vascular calcification (50). It is interesting that calciphylaxis, or calcific uremic arteriolopathy, has been reported with increasing frequency in patients who are treated with warfarin therapy (11).…”
Section: ) (B)mentioning
confidence: 99%